P105 Endocrine, autonomic and vascular function in children with Sleep Disordered Breathing. (7th October 2021) - Noone, A; Lushington, K; Kennedy, D; Martin, J; Vokolos, P; Wabnitz, D; Kontos, A
Abstract: SDB is a risk factor for cardiovascular disease and co-exists with chronic endocrine disorders such as type II diabetes and metabolic syndrome. Children with SDB have increased blood flow velocity, an indicator of reduced vascular compliance and early vascular aging. Increased blood flow velocity is positively associated with sympathetic activity, increased arterial sympathetic nerve fibre density and endothelial damage. Whether changes in endocrine function occur concomitantly with altered autonomic and vascular function in children with SDB was assessed. Thirty six children scheduled for tonsillectomy underwent overnight polysomnography (SDB severity), pupil light reflex (autonomic function), fasting brachial artery blood flow assessment (vascular function - Doppler Ultrasound). Leptin and Ghrelin - both hormonal markers associated with sympathetic activity were measured in urine using ELISA and serum using MagPlex. The following dimensions of the dorsal lingual artery (tonsil) were measured – medial thickness, medial area, smooth muscle cell number/layers. We observed a positive correlation between serum and urine leptin and ghrelin concentrations. Increased blood flow velocity and arterial medial thickness were both associated with increased serum and urine leptin and ghrelin concentrations. Pupil light reflex was negatively associated with serum leptin and ghrelin levels. OAHI was positively correlated with leptin and ghrelin concentration (urine and serum) but not blood flow velocity. Blood flow velocity was inversely correlated with SpO2 nadir (REM). Our findings suggest that SDB has a global effect on the autonomic, vascular and endocrine systems.The impact of untreated paediatric SDB on the development of comorbidities in later life needs urgent attention.